Clinical Status and Future Prospects of Transanal Total Mesorectal Excision - Guo, Zichao; Ji, Xiaopin; Wang, Shaodong; Zhang, Yaqi; Liu, Kun; Wang, Changgang; Deng, Yang; Zhang, Tao; Cheng, Xi; Zhao, Ren (Frontiers in Oncology, 2022)
Low rectal cancer has always posed surgical challenges to gastrointestinal surgeons. Transanal total mesorectal excision (taTME) is a novel approach to radical resection for low rectal cancer. Compared with conventional laparoscopic TME (laTME), taTME is relevant to the benefits of better vision of the mesorectal plane, feasibility of operating in a narrow pelvis, and exact definition of distal resection margin, which may lead to a higher possibility of free circumferential resection margin, better quality of TME specimen, and lower conversion rate. Although there are concerns about its long-term oncological outcomes and complex learning curve, taTME is a promising alternative for rectal cancer. In this review, we discuss the application status and prospects of taTME.